Influence of Blending Mode on Crystalline Morphology, Structure and Mechanical Behaviors of Isotactic Polypropylene/Poly(cis-butadiene) Rubber Blends - Sun, Hui; Yu, Bin; Wang, Jiajun (Asian Journal of Chemistry, 2014)
Isotactic polypropylene/poly(cis-butadiene) rubber (iPP/PcBR) blends with various blend ratio were prepared by two blending modes, the internal mixer and single screw extrusion, respectively. The single screw extrusion blending mode caused a more imperfect crystalline morphology and smaller spherulites. The increase of poly(cis-butadiene) rubber content and various blending modes did not affect the interplanar distance of the blends. The blends prepared by single screw extrusion had smaller crystal dimensions, higher the normalized relative degree of crystallinity and the polypropylene-b crystal content. The blends prepared by single screw extrusion had higher toughness and strength compare to those blended by the internal mixer